(untitled) - Plimpton, Laura (Irvine, Calif., 2007)
Minimize your legal risks and lock in profits as experienced contract attorney Laura Plimpton walks you through a fail-safe method of reviewing any contract. Learn to identify and neutralize the trick phrases that can create enormous risks for you and your business. Plimpton's expert advice can save you thousands of dollars in legal fees and may just prevent you from entering into a contract that could bankrupt your business.
Keywords: Contracts,Business enterprises,Các hợp đồng,Doanh nghiệp kinh doanh; Law and legislation,Luật và pháp chế; United States,United States,Hoa Kỳ,Hoa Kỳ